Investigation of the relationship between spiritual well-being and quality of life in breast cancer patients - Tsoho, Muhsina Adam; Soylar, Pinar (Springer Heidelberg, 2024)
AimThis study aimed to investigate the relationship between spiritual well-being and quality of life, for breast cancer patients.Subject and methodsThis cross-sectional study was conducted with 91 breast cancer patients treated at Firat University Hospital, Elazig/Turkey in 2021. A personal information form was used in the first part of the questionnaire. In the second part, the European Cancer Treatment and Organizing Committee Quality of Life Scale (EORTC QLQ-C30) was used to measure the quality of life (QoL) and the Spiritual Well-Being Scale (FACIT-Sp12) was used to measure the spiritual well-being of the breast cancer patients.ResultsThe mean age of patients was 54.38 +/- 11.68. The results showed that the participants had an overall global QoL score of 44.76 (SD = 18.96). Role function had the highest score (60.32 (SD = 8.87)) in functional sub-dimension. The highest score in symptoms sub-dimension belonged to pain (58.51 +/- 23.01) and financial impact (71.54 +/- 23.65). FACIT-Sp12 score of 24.79 (SD = 4.80). There is a positive relationship between each domain of FACIT-Sp12 and the QLQ-C30 (p < 0.005) except symptom sub-dimension. The correlation coefficient showed a negative correlation between symptom sub-dimension and each of the sub-dimensions of FACIT-Sp12 and the QLQ-C30 (p < 0.001).ConclusionThe results of our study showed that the level of quality of life and spiritual well-being of breast cancer patients were found to be poor. Considering the relationship between spirituality and quality of life, it is necessary to meet the needs of breast cancer with more psycho-spiritual interventions.
Keywords: Breast Cancer; Quality of life; Spiritual well-being; Patient